2010
DOI: 10.1261/rna.2537911
|View full text |Cite
|
Sign up to set email alerts
|

Widespread regulatory activity of vertebrate microRNA* species

Abstract: An obligate intermediate during microRNA (miRNA) biogenesis is an~22-nucleotide RNA duplex, from which the mature miRNA is preferentially incorporated into a silencing complex. Its partner miRNA* species is generally regarded as a passenger RNA, whose regulatory capacity has not been systematically examined in vertebrates. Our bioinformatic analyses demonstrate that a substantial fraction of miRNA* species are stringently conserved over vertebrate evolution, collectively exhibit greatest conservation in their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
245
0
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(267 citation statements)
references
References 79 publications
(123 reference statements)
14
245
0
8
Order By: Relevance
“…The role of miR* is sometimes ambiguous. Some miR* products can be functional (43,44), whereas the rest are unlikely to be so. The remaining two parts of the miRNA precursor, the loop end and the stem extension, are very unlikely to give rise to functional products.…”
Section: Discussionmentioning
confidence: 99%
“…The role of miR* is sometimes ambiguous. Some miR* products can be functional (43,44), whereas the rest are unlikely to be so. The remaining two parts of the miRNA precursor, the loop end and the stem extension, are very unlikely to give rise to functional products.…”
Section: Discussionmentioning
confidence: 99%
“…11,15,48,49 In plants, the specific sorting of miRNA* strands into AGO proteins were also observed, 16 whereas no systemic study on their activities has been performed.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…However, recent studies revealed some important biological functions of miRNA*s in both plants and animals. 44,58,[111][112][113][114] Here, based on the results obtained from our sRNA-seq-based bioinformatics analysis, we proposed that certain miRNA*s or isomiR*s could act as anti-miRs to inhibit the cognate miRNAs from binding the target transcripts, thus reducing the activities of the miRNAs. It is based on the following evidences: (1) According to the biogenesis model of the plant miRNAs, after DCL1-mediated 2-step processing, miRNA and its miRNA*, forming as a short RNA duplex, were exported to the cytoplasm for loading into the AGO1 complex.…”
Section: Degradome-seqmentioning
confidence: 99%